2005
DOI: 10.1507/endocrj.52.117
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Remission of Functioning Pituitary Adenomas without Hypopituitarism following Infarctive Apoplexy: Two Case Reports

Abstract: Abstract. Functioning pituitary adenomas may exhibit spontaneous remission after pituitary apoplexy usually in association with hypopituitarism. We report two patients who presented with sudden headache and double vision, showed a ring-enhanced sellar tumor on MRI, underwent transsphenoidal surgery that revealed a coagulation necrotic adenoma without massive hemorrhage, and showed normal pituitary function after the surgery. Definitive diagnoses were made based on immunohistochemistry of the necrotic cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
1
15
1
4
Order By: Relevance
“…7,19,23,24 Theories about the underlying pathophysiology state that sudden alterations of perfusion pressure might predispose the tumor to infarction. 15 In consistency with these reports, we found that tumors with cystic or posthemorrhagic changes showed additional postoperative volume reduction more frequently than those without such changes.…”
Section: Discussionmentioning
confidence: 99%
“…7,19,23,24 Theories about the underlying pathophysiology state that sudden alterations of perfusion pressure might predispose the tumor to infarction. 15 In consistency with these reports, we found that tumors with cystic or posthemorrhagic changes showed additional postoperative volume reduction more frequently than those without such changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of spontaneous biochemical remission after PA have been reported for GH-secreting (120,121,122), ACTH-secreting (18,123,124) and prolactin-secreting (122) tumours. However, in a large case series, 90% of the functioning tumours remained active following PA, the majority of which required surgery (19).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In patients with a functioning adenoma, recurrence after the initial biochemical cure is possible (18,123,125,126), necessitating long-term follow-up. In a series of NFPA presenting with apoplexy, treated surgically and followedup for a mean period of 6.6 years, the regrowth rate was 11%.…”
Section: Recurrencementioning
confidence: 99%
“…In our patients, however, cabergoline had been stopped 2.5-5.5 years making this possibility unlikely. Adenoma infarction or apoplexy either spontaneous or induced by dopamine agonist therapy has been described [24][25][26], but the patients had no history of headaches and no change in tumour size or characteristics was visible on MRI. Apoptosis of tumoral cells induced by the medication is probably one likely mechanism, as evidenced in prolactinomas [27].…”
Section: Discussionmentioning
confidence: 95%